From nature back to nature: Spectrally modified poplar and its all-day passive radiative cooling - She, Yanan; Wang, Jing; Zhu, Chunfeng; Tian, Feiyu; Jin, Yuanyuan; Mao, Wei; Wu, Yutao; Chen, Kai; Xu, Xinwu (Industrial crops and products, 2023)
Thermal radiation properties of natural wood are mainly affected by its chemical composition and physical structure. In the atmospheric transparency window (8–13 µm), cellulose, hemicellulose and lignin all have high average emissivity of 95.77%, 96.83% and 97.22%, respectively. This allows wood to continuously transfer radiation heat to outer space without hindrance, according to natural radiative cooling principle. It is so attractive to develop its all-day radiative cooling potential for continuous heat dissipation and energy-saving without energy input and pollutant output. Cooling capacity is directly affected by spectral property, for which delignified wood is prepared to explore the relation between lignin content and thermal radiation properties of wood. Results show that, the lower lignin content of wood would cause the higher average solar reflectivity and daytime radiative cooling power density, without affecting infrared emissivity and nighttime radiative cooling performance. With lignin content of 0.94%, delignified wood achieves all-day radiative cooling performance, obtaining average temperature drop of 2.60 K and 3.81 K at daytime and nighttime. Magically, its surface has a redirecting effect on incident heat, to the credit of the removal of amorphous lignin and inherited cellulose arrangement. Such a light-weight, environment-friendly, low-cost and all-day energy-saving material combining natural wood and natural radiative cooling principle provides a novel option for green products. [Display omitted] •Natural wood and natural principle are combined for green products.•Thermal radiation properties of natural poplar are comprehensively explored.•Spectrally modified wood has high infrared emissivity and adjustable reflectivity.•Lignin content is highly related with reflectance and cooling capacity of wood.•Delignified wood can achieve all-day radiative cooling performance.